The influence of channel network silting up at Žitný Ostrov to range of interaction between surface and groundwater - Dulovičová, Renáta; Velísková, Yvetta (Acta Agraria Debreceniensis, 2020)
The movement of water resources, especially the possibilities of their regulation by interaction between surface and groundwaters are the subject matter of attention particularly during the occurrence of extreme hydrologic situation. This work presents the overview of knowledge and results which were achieved at IH SAS in this question. It can show the ways how to optimize the adjudicated processes which emerge during the requirement of emergency intervention. The solution of this task was located at the Žitný Ostrov area because this territory with their existence of channel network is suitable for studying the surface and groundwater interaction. The channel network at Žitný Ostrov was built up for drainage and also to safeguard irrigation water. The water level in the whole channel network system has an effect on groundwater level on the Žitný Ostrov and vice versa. It was been necessary to judge the impact of the channel network silting up by bed silts on the interaction between channel network and groundwater on the Žitný Ostrov. The aim was to evaluate the changes of bed silt state of Žitný Ostrov channel network and consecutively their influence on interaction processes between groundwater and surface water along the channels in the period from 1993 to present. The measurements of bed silt thickness in Žitný ostrov channel network had been started from1993, later they continued at selected profiles of three main channels – channel Gabčíkovo-Topoľníky, Chotárny channel and Komárňanský channel (for checking of the silting up variability). From 2008 the detailed field measurements of cross-section profiles aggradations along these selected three channels have been started. The objective of detailed field measurements was the determination of the silt permeability which is expressed by parameter of saturated hydraulic conductivity. This parameter was determined by two ways – as the saturated hydraulic conductivity obtained from disturbed samples of silt Kp and as the saturated hydraulic conductivity obtained from undisturbed samples of silt Kn. In the first case the granularity of silts was determined as a first step and then was computed their Kp from the empirical formulas according Bayer-Schweiger and Spacek. From undisturbed samples of silts which were extracted along the channels from top, middle and bottom layer of silts, were determined the values Kn by the laboratory falling head method. The valid values Kp on channel Gabčíkovo-Topoľníky ranged from 4,33 10-7 to 4,46.10-5 m s-1, on Chotárny channel from 5.98 10-5 to 2.14 10-6 m s-1 and on Komárňanský channel fluctuated from 1.93 10-6 – 6.09 10-5 m s-1. The valid values Kn on on channel Gabčíkovo-Topoľníky ranged from 5.21 10-8 – 4.18 10-3 m s-1 , on Chotárny channel ranged from 8.54 10-8 – 2.70 10-4 m s-1 and on Komárňanský channel fluctuated from 4.72 10-7 – 1.26 10-5 m s-1. The remarkable results were noticed by comparison of values of saturated hydraulic conductivity from disturbed and undisturbed samples Kp and Kn. On Chotárny channel the values of silt saturated hydraulic conductivity from undisturbed samples Kn approximately hundredfold decreased (from 10-6 to 10-8 m s-1). On Komárňanský channel the comparison of values Kp and Kn shown that the values Kn from undisturbed samples approximately tenfold descended against Kp. Simultaneously, the bed silts‘ impact on the groundwater recharge (saturated hydraulic conductivity of silt) was also examined. Determination of the total recharge amount was done by numerical simulation (model SKOKY) and by the so-called method of interaction formulas. These two approaches were applied at the Žitný Ostrov channel network. There were field measurements performed in monitored three main channels and adjacent to obtain correct input data. These characteristics were used for simulation and computation of total recharge along the channels. The total recharge amount was calculated for four alternatives of the surface water levels in the channel and the surroundings groundwater respectively. We chose four simplified variants with the same geological conditions in surroundings area of channels, only water levels of groundwater and in channels were modified. The results of the simulations seem to show greater impact of the silt in the case of outflow from the channels to the surroundings than the inflow into the channel from the surroundings.